Factor‐inhibiting hypoxia‐inducible factor expression in patients with high‐risk locally advanced renal cell carcinoma and its relationship with tumor progression. Issue 1 (16th August 2013) - Deng, Shi; Zhang, Peng; Zeng, Hao; Wang, Wei; Jin, Tao; Wang, Jia; Dong, Qiang
Abstract: Hypoxia‐inducible factor (HIF) plays an important role in renal cell carcinoma (RCC) associated with angiogenesis. Factor‐inhibiting HIF (FIH), which is the upstream mediator protein of HIF, is receiving more attention today. In the present study, the role of FIH expression in high‐risk locally advanced renal cell carcinoma (LARCC) was explored. Eighty‐eight high‐risk LARCC cases were divided into two groups based on their prognosis. Using immunohistochemical staining, the correlations of FIH expression along with clinicopathological factors, progression‐free survival (PFS), and overall survival (OS) were analyzed. FIH was mainly located in the cytoplasm (34/88) and nucleus (31/88) of the renal tumor cell. Nuclear negative expression or cytoplasmic positive expression of FIH were associated with an increased risk of disease progression ( p  = 0.007 and p  < 0.001, respectively) and worse OS ( p  = 0.020 and p  = 0.008, respectively). Using the group with nuclear and cytoplasmic FIH negative expression as reference, further stratified analysis found that the exclusive nuclear FIH expression group had a better PFS and OS [hazard ratio (HR) = 0.153, p  = 0.07 and HR = 0, p  = 0.961, respectively], and the exclusive cytoplasmic FIH positive group experienced the worst PFS and OS (HR = 2.876, p  = 0.005 and HR = 2.799, p  = 0.034, respectively). In addition, nuclear negative expression of FIH was associated with a significant negative predictive value for the effect of interferon‐alpha (IFN‐α) on PFS ( p  = 0.045). The nuclear negative and cytoplasmic positive expressions of FIH were identified not only as risk factors for disease progression in high‐risk LARCC postoperative patients, but also to be associated with poor OS. Furthermore, the nuclear negative expression of FIH may be a promising biomarker for postoperative adjuvant therapy.